Prevalence and risk factors of dermatoporosis in older adults in a rehabilitation hospital. Issue 4 (17th December 2021) - Chanca, Laura; Fontaine, Juliette; Kerever, Sébastien; Feneche, Yohann; Forasassi, Christine; Meaume, Sylvie; Colboc, Hester
Abstract: Background: The term dermatoporosis (DP) is used to describe the clinical signs and functional consequences of age‐related extreme skin fragility. It is associated with potentially severe complications, including deep dissecting hematomas and extended skin lacerations. No studies have evaluated the prevalence and risk factors of DP in adults aged 75 and older. Methods: The aim of our study was to assess the prevalence, complications, and risk factors of DP in a cohort of older patients hospitalized in a rehabilitation center. A case–control, single‐center study was conducted between September and October 2020 in our rehabilitation ward, Rothschild Hospital, Paris, France. A senior dermatologist and a resident in geriatric medicine performed a systematic dermatological examination. The presence of DP, its stage, its location, and complications were collected, as were demographical data, comorbidities, past sun exposure, skin phototype, treatments, and biological data. Results: A total of 101 patients (62 women, median age 86 years [extreme values 75–104]) were included. The overall prevalence of DP was 27%. Stage 1 was the most frequent. DP was mainly located on the upper limbs. Ten (37%) patients had a DP complication: eight (30%) skin lacerations and two (7%) deep dissecting hematomas. Multivariate analysis revealed a significant association between DP and age (odds ratio [OR] 5.82, 95% confidence interval [CI] 1.67–24.92, p  = 0.009), smoking (OR 8.67, 95% CI 2.59–34.85, p  = 0.001), recreational sun exposure (OR 4.23, 95% CI 1.30–15.21, p  = 0.02), and anticoagulant therapy (OR 4.53, 95% CI 1.32–17.26, p  = 0.02). Conclusion: Our study is the first to analyze the prevalence and risk factors of DP in older adults in rehabilitation. Frequency of DP makes it relevant for the geriatrician and should be described more to prevent potential severe complications. A multicentric study, with inpatients and outpatients, could evaluate the prevalence of DP in a more representative older adult population.